Mucoepidermoid (adenosquamous) carcinoma, trichoblastoma, trichilemmoma, sebaceous adenoma, tumor of follicular infundibulum and syringocystadenoma papilliferum arising within 2 persistent lesions of nevus sebaceous: Report of a case - Jane Manonukul (2018)
Nevus sebaceous of Jadassohn (SNJ) is a congenital, hamartoma of multiple skin structures and may classically evolve through several stages of maturation. Many neoplasms have been reported to arise in association with SNJ, most commonly trichoblastoma and syringocystadenoma papilliferum. The coexistence of 3 or more tumors arising simultaneously within 1 lesion of SNJ is very rare. We report a case of a 66-year-old woman with a coexistence of trichoblastoma, trichilemmoma, sebaceous adenoma, tumor of follicular infundibulum, syringocystadenoma papilliferum, and mucoepidermoid or adenosquamous carcinoma arising in 2 separate and persistent SNJ exhibiting on her face with subsequent parotid node metastasis. This report illustrates an extraordinary case of adnexal neoplasms displaying diverse lines of differentiation arising within lesions of SNJ. We also reported the second instance of mucoepidermoid arising within the lesion of SNJ and also added sebaceous adenoma to the list of sebaceous tumors arising within this lesion. Prophylactic excision or at least close clinical surveillance for sudden development of new growths is warranted. © 2009 Lippincott Williams & Wilkins, Inc.